Mortality and condition factor of juvenile green catfish (Hemibagrus nemurus c.v) on different bottom substrat - . Dualantus; Ricky Djauhari (Jurnal Akuakultur Indonesia)
The research was aimed to determine the type of substrate that is suitable for juvenile of green catfish in a container after transportation. This research used completely randomized design with 3 treatments and 3 replications.  Treatments are bottom substrates of white sand, 1 inch piece of  PVC pipes, and pieces of the tree roots submerged in river water. The result of the analysis of survival rate data variability of green catfish juvenile showed no significantly different among treatments. Similar result was also showed in mortality rate that was not affected by substrate type used. Thus, substrates of white sand, 1 inch piece of PVC pipes and tree roots submerged in water provided similar opportunity to green catfish to survive. The range of condition factor obtained was 2.3 to 3.9. That value was in the common range, which means that the weight gain was greater than the length.